2003
DOI: 10.1115/1.1535190
|View full text |Cite
|
Sign up to set email alerts
|

Drilling in Bone: Modeling Heat Generation and Temperature Distribution

Abstract: Thermo-mechanical equations were developed from machining theory to predict heat generation due to drilling and were coupled with a heat transfer FEM simulation to predict the temperature rise and thermal injury in bone during a drilling operation. The rotational speed, feed rate, drill geometry and bone material properties were varied in a parametric analysis to determine the importance of each on temperature rise and therefore on thermal damage. It was found that drill speed, feed rate and drill diameter had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
176
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(186 citation statements)
references
References 26 publications
8
176
2
Order By: Relevance
“…Likewise, Hillery and Shauib (Hillery and Shuaib 1999) detected no significant difference in temperature elevation in bovine and cadaveric bone in vitro when testing point angles of 70˚, 80˚ and 90˚. Numerical models have also suggested point angle to have a negligible effect on the maximal temperature attained during drilling (Davidson and James 2003). Ostensibly, a lower limit to the point angle which can be accommodated by 2-fluted drills without compromising the structural integrity of the point exists but which has not been described.…”
Section: Anatomy Of a Drill-bitmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, Hillery and Shauib (Hillery and Shuaib 1999) detected no significant difference in temperature elevation in bovine and cadaveric bone in vitro when testing point angles of 70˚, 80˚ and 90˚. Numerical models have also suggested point angle to have a negligible effect on the maximal temperature attained during drilling (Davidson and James 2003). Ostensibly, a lower limit to the point angle which can be accommodated by 2-fluted drills without compromising the structural integrity of the point exists but which has not been described.…”
Section: Anatomy Of a Drill-bitmentioning
confidence: 99%
“…Natali and colleagues suggested the optimal helix angle for surgical drill-bits to be approximately 36° (Natali, Ingle et al 1996), actually rendering it a fast helix. The helix angle of a drill-bit has implications for both rake angle and torsional rigidity (Narasimha, Osman et al 1987) but has little effect on the maximal temperature elevation (Davidson and James 2003). Narasimha and co-workers (Narasimha, Osman et al 1987) demonstrated that torsional rigidity varies parabolically with helix angle, reaching a maximum at approximately 28˚.…”
Section: Anatomy Of a Drill-bitmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the frictional contact between a drill and cortical bone was modeled with a constant coefficient of friction of 0.7 [17]. The models require on average 54 h on 36 Intel quad-core processors with 48 GB RAM each to finish the analysis using High Performance Computing (HPC) facility available at Loughborough University.…”
Section: Boundary Conditions and Contact Interactionsmentioning
confidence: 99%
“…Different models have been developed [11,[21][22][23][24][25][26][27][28] with the aim of reproducing the behaviour of cortical bone. In this work, cortical bone of bovine femur is used as a reference and the numerical results are compared with the experimental data in the literature.…”
Section: Modeling Behaviour Of Cortical Bonementioning
confidence: 99%